Indirect calorimetry in hemodinamic and metabolic monitoring in dogs under different hemodynamic states Calorimetria indireta na monitoração hemodinâmica e metabólica em cães sob diferentes situações hemodinâmicas - Gehrcke M.I.* (2015)
Monitoring the hemodynamic state seeks a balance between the supply and demand of oxygen by tissues. The aim of this study was to evaluate the use of indirect calorimetry (IC) compared to thermodilution (TD) in dogs under different hemodynamic states. Nine dogs weighing 19.6±1.3kg were anesthetized with isoflurane at 1.4 V% (Baseline) and subjected to mechanical ventilation (MV), a hypodynamic state (Hypo) with isoflurane at 3.5V% and hyperdynamic state (Hyper) with dobutamine infusion at 5μg/kg/min. We used a Swan-Ganz catheter for measurement of cardiac index (CI) by TD, calculation of oxygen consumption by Fick's method (VO2 Fick) and to collect central and mixed venous blood. With the IC we obtained oxygen consumption (VO2), CO2 production (VCO2) and end tidal CO2 (EtCO2). For the determination of CI by IC we used the Fick's principle with VO2 values, and arterial and mixed venous blood (Fickmix) or arterial and central venous blood (Fickvc); and by the ratio of the values of VCO2 and EtCO2 (FickCO2). We performed the statistical analysis by Dunnet tests, for the difference between the states, and Tukey for differences between methods (P≤0.05). Pearson correlation and Bland-Altman analysis was performed for correlation and agreement analysis. IC provided VO2 values 30 to 40% higher than the VO2 Fick but identified the reduction in VO2 after VM and Hypo, which did not occur with VO2 Fick. The VCO2 values decreased in VM and Hypo. CI values decreased in Hypo with all methods and increase in Hyper with TD and Fickvc. The CI values for Fickmix and Fickvc were greater than TD at all times and FickCO2 was lower than TD in the Hyper. None of the methods presented agreement and correlation with TD. Thus, indirect calorimetry can be used to measure the VO2 and VCO2 in dogs in different hemodynamic states. However, although it is possible to identify the hemodynamic status, cardiac index values cannot be compared to thermodilution.